The Effect of Influencer Marketing Effectiveness on Purchase Intention of Skintific among Students of Universitas Negeri Jakarta - Mohammad Akeyla Zedidiah; Adnan Kasofi; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
The purpose of this study is to examine how Universitas Negeri Jakarta students' purchase intentions for Skintific skincare products are impacted by the efficacy of influencer marketing. This study uses a survey method and a quantitative methodology. Multiple linear regression analysis was used to evaluate the data obtained from 108 respondents via an online questionnaire. The findings indicate that while trust in influencers has a favorable and significant impact on purchase intention, influencer consistency and attractiveness do not. At the same time, buy intention is greatly influenced by influencer consistency, attractiveness, and trust. According to the coefficient of determination, the independent factors account for 75.1% of purchase intention. These results imply that the most important component of influencer marketing tactics for skincare products aimed at college students is trust.